ANALISIS MODEL PEMBELAJARAN PROBLEM BASE LEARNING (PBL) PADA MATERI SEJARAH PERKEMBANGAN MUSIK KELAS 8 DI SMP NUSAPUTERA SEMARANG - Ade Rahma Dyan WP; Siti Aesijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the phenomenon of low student engagement at SMP Nusaputera Semarang in participating in music learning, particularly in theoretical subjects such as the History of Music Development. This condition is characterized by limited student participation in discussions, minimal responses to teacher questions, and a tendency for students to remain passive during the learning process. This research aims to analyze how the Problem-Based Learning (PBL) model can optimize students' critical thinking skills in the topic of the History of Music Development. This study employs a descriptive qualitative research method to describe how the PBL syntax can develop the critical thinking skills of eighth-grade students. The results show that the implementation of the Problem-Based Learning (PBL) model is able to stimulate students' cognitive abilities in identifying the characteristics of musical works in each era, as well as providing examples of composers and well-known works from each period. Group discussion activities and independent inquiry in PBL have proven to encourage active student engagement and develop students’ critical thinking skills in a deeper and more systematic way.